An examination of activity in public and private hospitals in Ireland, 2015 - Conor Keegan; Aoife Brick; Maev-Ann Wren (The Economic and Social Research Institute (ESRI), 2018)
This analysis examines the extent to which activity in public hospitals is privately financed and provides an overview of service delivery across public and private hospitals in Ireland in 2015. This analysis was conducted in light of a Sláintecare proposal to remove private practice from public hospitals and the establishment of an Independent Review group to examine this proposal in detail. Overall we find that just under 16 per cent of cases were privately financed in public hospitals in 2015. Across public and private hospitals, fewer than one-in-four private day patient episodes were estimated to have taken place in public hospitals. In comparison, over 50 per cent of private in-patient bed days were recorded in public hospitals. These findings suggest that the private hospital system appears to have primarily specialised in the delivery of elective care. It is unclear therefore whether the majority of private in-patients in public hospitals, who are emergency in-patients, could access the care they may require in private hospitals. It is acknowledged that a barrier to more detailed comparative analysis is the lack of a centralised administrative system to collect private hospital activity data.
Keywords: 330